THE FATTY ACID AND MINERAL COMPOSITIONS OF DIFFERENT CHICKPEA CULTIVARS CULTIVATED - Kaya, Muharrem; Kan, Asuman; Yilmaz, Azime; Karaman, Ruziye; Sener, Aykut (PARLAR SCIENTIFIC PUBLICATIONS (P S P), 2018)
In this study, crude oil content, fatty acid and mineral composition of different chickpea varieties cultivated in Konya were investigated. Fatty acid (saturated and unsaturated) compositions, crude oil and mineral contents were determined; GC-MS, Soxhelet-Henkel and ICP-OES, respectively. There were significant (p<0.01) differences between the chickpea cultivars in view of their crude oil contents and fatty acids (saturated and unsaturated) compositions. The oil yields of the nineteen chickpea cultivars varied between 2.91 and 6.43%. The highest crude oil content was determined in Gokce (6.43%) cultivar. On the other hand, highest compositions of the unsaturated fatty acids were determined in Uzunlu 99 (88.01%). Furthermore, the total compositions of the highest saturated fatty acids were determined in Camtez 87 (17.71%). The linolenic (in ILC 482, 2.68%), linoleic (in ILC 482, 57.25%) and oleic (in Gtiliimser, 42.30%) acids were dominating fatty acids of the cultivars. According to the results, the total macro element composition of the chickpea cultivars were found to range from 16267 to 23634 and K and P were the dominating macro elements of the cultivars. Moreover, the micro element composition of the chickpea cultivars varied from 165.36 to 269.09 Fe and B were the highest micro elements of the cultivars.
Keywords: Chickpea; crude oil; fatty acid; mineral compositions; CICER-ARIETINUM L.; ELEMENT CONTENTS; PAKISTAN; TURKEY; SEEDS; OIL; Environmental Sciences & Ecology